PENDIDIKAN AKHLAK SEBAGAI UPAYA PENCEGAHAN KENAKALAN REMAJA - Achmad Mudzaki Dinata (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2024)
Moral education is a very important axis as an effort to prevent juvenile delinquency, in addition to moral education there are also other efforts such as 5S habituation, routine worship habits, requiring extracurricular activities and youth development must also go hand in hand. If it is not accompanied by other efforts, it will still be more difficult to prevent juvenile delinquency and also the role of parents in supervising teenagers is an important point so that juvenile delinquency can be eradicated. This study aims to determine the problems of juvenile delinquency experienced by adolescents and the implementation of moral education on juvenile delinquency. This research uses descriptive qualitative research methods through interviews, literature studies and questionnaires, in order to obtain concrete and relevant data in accordance with the research objectives. The object of research is adolescents who have committed juvenile delinquency and have never committed juvenile delinquency. The results of the study stated that teachers' efforts to instill moral education to prevent juvenile delinquency consisted of 5 things, namely internalizing moral education, coaching adolescents, extracurricular programs, habituating worship, and habituating 5S.